2012
DOI: 10.5301/ejo.5000206
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Retinal Nerve Fiber Layer Thickness in Children with Iron Deficiency Anemia

Abstract: Mean age of each group was 11.3±2.7 years. Average RNFL and RNFLs of superior and inferior quadrants were significantly thinner in the anemic group than in the control group (p=0.006, p=0.005, and p=0.005, respectively). In addition, average peripapillary RNFL thickness and RNFL thicknesses of superior, inferior, and temporal quadrants were correlated with hemoglobin levels (r1=0.734, p1<0.001, r2=0.456, p2=0.005, r3=0.598, p3<0.001, r4=0.349, p4=0.037, respectively) in anemic group. CONCLUSIONS. We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 27 publications
0
21
0
3
Order By: Relevance
“…In contrast, children with iron deficiency anaemia have been found to have lower average, superior and inferior RNFL thicknesses compared with controls. 7 A further study evaluating RNFL thicknesses in children with thalassaemia major or iron deficiency anaemia showed that RNFL thicknesses were decreased in all quadrants in children with thalassemia major, but in the inferior quadrant only in children with iron deficiency anemia. 8 The inconsistencies between these studies and our own may be a result of differences in the study populations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, children with iron deficiency anaemia have been found to have lower average, superior and inferior RNFL thicknesses compared with controls. 7 A further study evaluating RNFL thicknesses in children with thalassaemia major or iron deficiency anaemia showed that RNFL thicknesses were decreased in all quadrants in children with thalassemia major, but in the inferior quadrant only in children with iron deficiency anemia. 8 The inconsistencies between these studies and our own may be a result of differences in the study populations.…”
Section: Discussionmentioning
confidence: 97%
“…5 The spectral domain OCT technique provides faster acquisition, better resolution and improved imaging of retinal morphology than traditional OCT. 6 In children with thalassaemia major and/ or iron deficiency anaemia, OCT studies found that RNFL thicknesses decreased, relative to reduced haemoglobin and ferritin concentrations. 7,8 To the best of our knowledge, RNFL thickness in adult women with iron deficiency anaemia has not been studied. The aim of the present study, therefore, was to evaluate RNFL thickness in adult women with iron deficiency anaemia, and in age-and sex-matched healthy control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was consistent with previous study. 10 These results suggest that a decreased hemoglobin level is associated with RNFL thinning and ganglion cell loss. However, glaucomatous optic disc cupping or notching in these patients was not observed.…”
Section: Discussionmentioning
confidence: 80%
“…The association between ischemic injury and ganglion cell loss has been investigated, 9 but the association between anemia and ganglion cell loss has not been examined. Turkyilmaz et al 10 reported that peripapillary retinal nerve fiber layer (RNFL) thickness was decreased in children with iron deficiency anemia, and RNFL thickness was significantly correlated with hemoglobin levels. To investigate the association between chronic anemia and ischemic optic neuropathy, investigation of RNFL profile in patients with hematologic malignancy would be ideal because these patients have their hemoglobin level measured often, and they often have a history of severe anemia during their treatment course.…”
mentioning
confidence: 99%
“…And there was statistically significant correlation between mean RNFL, upper, lower, and temporal quadrant RNFL thickness and average values of hemoglobin. [19] Further study by Aksoy et al to evaluate RNFL thickness in children with thalassemia major and children with iron deficiency anemia, detect that RNFL thickness was decreased in inferior quadrant in IDA group and there was positive correlation between RNFL thickness and hemoglobin level. While in thalassemia major group, RNFL was decreased in all four quadrants compared to the control and IDA group.…”
Section: Discussion:-mentioning
confidence: 99%